High expression of KIBRA in low atypical protein kinase C‐expressing gastric cancer correlates with lymphatic invasion and poor prognosis. Issue 2 (27th December 2012) - Yoshihama, Yohei; Izumisawa, Yusuke; Akimoto, Kazunori; Satoh, Yoshinori; Mizushima, Taichi; Satoh, Kei; Chida, Kazuhiro; Takagawa, Ryo; Akiyama, Hirotoshi; Ichikawa, Yasushi; Kunisaki, Chikara; Inayama, Yoshiaki; et al.
<x xml:space="preserve">Abstract</x> Overexpression of atypical protein kinase Cλ/ι (aPKCλ/ι), a regulator of cell polarity, is frequently associated with the poor prognoses of several cancers, including gastric cancer. Recent studies revealed a molecular link between aPKC and KIBRA, an upstream regulator of tumor suppressor Hippo pathway that regulates cell proliferation and apoptosis. Further, KIBRA directly inhibits the kinase activity of aPKC to regulate epithelial cell polarity. These observations suggest that the KIBRA‐aPKC connection plays a role in cancer progression; however, clinical significance of the correlation between these factors remains unclear. Here we examined the correlation between KIBRA/aPKCλ/ι expression, as detected by immunohistochemistry, and clinicopathological outcomes in 164 gastric cancer patients using Fisher's exact test and Kaplan–Meier log‐rank test. We found an intimate correlation between the expression level of KIBRA and aPKCλ/ι (P = 0.012). Furthermore, high expression of KIBRA is correlated with lymphatic (P = 0.046) and venous invasion (P = 0.039). The expression level of KIBRA by itself did not correlate with the prognosis; however, high expression of KIBRA in low aPKCλ/ι‐expressing gastric cancer correlated with disease‐specific (P = 0.037) and relapse‐free survival (P = 0.041) by Kaplan–Meier with log‐rank test and higher lymphatic invasion cases by Fisher's exact test (P = 0.042). Furthermore, overexpression of the aPKC‐binding region of KIBRA disrupted tight junctions in epithelial cells. These results suggest that high expression of KIBRA in low aPKC‐expressing cells causes massive loss of aPKC activity, leading to loss of polarity and invasiveness of gastric cancer cells.